Ultra-rare renal diseases diagnosed with whole-exome sequencing: Utility in diagnosis and management - Jiwon Jung; Joo Hoon Lee; Young Seo Park; Go Hun Seo; Changwon Keum; Hee Gyung Kang; Hajeong Lee; Sang Koo Lee; Sang Taek Lee; Heeyeon Cho; Beom Hee Lee (BMC, 2021)
Abstract Background This study aimed to use whole-exome sequencing (WES) to diagnose ultra-rare renal diseases and the clinical impact of such an approach on patient care. Methods Clinical, radiological, pathological, and genetic findings were reviewed in the patients and their family members. Results Nine patients from nine unrelated Korean families were included in the study and evaluated. WES identified eight different conditions in these patients, i.e., autosomal dominant tubulointerstitial kidney disease associated with UMOD mutation; recurrent urinary stones associated with APRT deficiency; Ayme-Gripp syndrome associated with MAF mutation; short rib-thoracic dysplasia associated with IFT140 mutation; renal coloboma syndrome associated with PAX2 mutations; idiopathic infantile hypercalcemia associated with CYP24A1 mutation; and hypomagnesemia associated with TRPM mutation. Eleven different mutations, including seven novel mutations, were identified, i.e., four truncating mutations, six missense mutations, and one splice-acceptor variant. After genetic confirmation, strategies for the management of the following: medications, donor selection for renal transplantation, and surveillance for extra-renal manifestations were altered. In addition, genetic counseling was provided for the patients and their family members with respect to family member screening for affected but yet unidentified patients and future reproductive planning. Conclusion As WES can effectively identify ultra-rare genetic renal diseases, facilitate the diagnosis process, and improve patient care, it is a good approach to enable a better understanding of ultra-rare conditions and for the establishment of appropriate counseling, surveillance, and management strategies.